A COMPLETE DUPLICATED SYSTEM WITH INTRAVESICAL URETEROCELE IN A 60-YEARS-OLD WOMAN: A CASE REPORT - Hady Prabowo, Satria Adji; Budaya, Taufiq Nur; Kustono, Andri (Indonesian Urological Association, 2025)
Objective: This case report presents a 60-year-old woman with intravesical ureterocele complicated by severe right upper-moiety hydronephrosis. Case(s) Presentation: A 60-year-old woman came with the chief complaint of right flank pain radiating to the umbilicus and groin accompanied by nausea, vomiting and decreased appetite. Ultrasound examination showed severe hydronephrosis of the right kidney. Abdominal CT revealed a double collecting system with severe hydroureteronephrosis at the upper pelvicalyceal system and the presence of an intravesical ureterocele. Cystoscopy and right RPG of upper and lower moiety procedures were performed and showed right severe hydroureteronephrosis with stenosis of right upper moiety ureteral orifice and ureterocele, followed by uroterocele incision and upper moiety ureteral re-implantation. No further complaints or complications were found after discharge from the hospital. Discussion: Adult ureterocele is a rare congenital anomaly often detected incidentally or due to complications like obstruction and infection. Diagnosis relies on imaging modalities such as ultrasonography, intravenous urography, and CT urography, while treatment options range from minimally invasive endoscopic decompression to surgical excision, depending on severity and associated complications. Conclusion: Ureterocele is a rare congenital urological abnormality found in non-Caucasians. Due to the rarity of the case, a thorough examination is required to establish this diaand the choice of the appropriate treatment procedure. The managements include incision of ureterocele and ureteroneocystostomy. Keywords: Adult ureterocele, intravesical ureterocele, hydronephrosis, complete double collecting system, vesicoureteral reflux